Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Nelayan Tangkap - Revalina Madingo; Usman Moonti; Radia Hafid; Frahmawati Bumulo; Melizubaida Mahmud (State University of Gorontalo, 2023)
This is a descriptive quantitative study with a population of 50 fishermen. The data collection technique uses a questionnaire, and the data analysis technique uses multiple regression analysis. The finding shows that the factor of capital and work experience have a positive effect on the income of fishermen in Bolaang Uki Sub-district, Bolaang Mongondow Selatan Regency. The coefficient of determination (R2) is 36% of the capital and work experience variables on the income of capture fishermen in Bolaang Uki Sub-district, Bolaang Mongondow Selatan Regency, while the remaining is affected by variables which are not described in this study.